PENGAKUAN DAN PENGUKURAN BELANJA SUBSIDI ENERGI BERBASIS AKRUAL – STUDI KASUS TAHUN 2015 - Mabrur, Azas; Siswanto, siswanto (Politeknik Keuangan Negara STAN, 2017)
Subsidy spending has a large share in the state budget (APBN). Thereby affecting the audit results by Supreme Auditor on government financial reports (LKPP). with the implementation of accrual-based government accounting in 2015, subsidy spending not only records transactions/activities based on cash flow but also non-cash transaction such as subsidy expenses and subsidy payable. This study aims to determine the implementation of the accrual basis on the accounting of energy subsidy spending.This study examines whether the recognition and measurement of energy subsidy spending, energy subsidy expenses and energy subsidy obligations have been presented in accordance with accrual-based government accounting standard and whether the recognition and measurement issues set out in the relevant Ministry of Finance Regulation (PMK) are in conformity with the accrual basis of accounting principles.The results show that the accounting of energy subsidy spending has been implemented in accordance with the PMK. However, the results also show that the PMK that regulates the accounting and financial reporting system of accrual-based subsidy spending still needs improvement.The necessary improvements are related to the recognition of subsidy expense over a period, the measurement of subsidy expenses, and the mechanism of subsidy payable disposal.